Appreciations and practices of digital citizenship in the Andean community - Suing, Abel; Alarcon-Llontop, Luis-Rolando; Bizberge, Ana (Frontiers in Communication, 2024)
Digital citizenship implies people's participation in managing their rights and civic engagements. However, definitions clash with reality due to institutional conditions, perceptions, and limited information literacy skills. In this context, it is of interest to determine the perceptions, forms of intervention and treatment of the concept of digital citizenship from the perspectives of citizens and the media in the Andean countries (Bolivia, Colombia, Ecuador, and Peru). The methodology is qualitative and quantitative with a descriptive scope. The research techniques used are a survey, semistructured interviews and content analysis. 497 people from the Andean countries responded to an online questionnaire between 16 June and 23 July 2023. Participants were selected on the basis of nonprobabilistic sampling. The semi-structured interviews were conducted between 15 and 30 May 2023 through Zoom; and the sample of newspaper articles corresponds to quotas. It is concluded that the media and social networks are effective tools for citizen participation, but it is suggested that the agendas to be revised to include the voices of the protagonists. There is a predominance of an instrumental conception, and social networks have been valued as means of communication. Andean inhabitants show resistance to the defence of rights or the management of social change, which could be fostered through a conscious and broad exercise of digital citizenship.